Case Report: The crucial role of contrast-enhanced ultrasound and intraoperative ultrasound in diagnosing pediatric pancreatoblastoma - Zeng, Xiangfeng; Yan, Hualin; Yang, Jiali; Xiang, Bo; Liu, Juxian (Frontiers in Oncology, 2025)
Pancreatoblastoma (PB) is a rare malignant neoplasm of the pancreas, primarily affecting children. While some reports have described the imaging characteristics of PB, detailed descriptions of its ultrasound (US) and contrast-enhanced ultrasound (CEUS) features in children are limited. We reported two cases of PB admitted to our hospital with detailed ultrasonographic features. The first case involved a 14-year-old girl who presented with intermittent, unexplained epigastric pain. CEUS revealed a hypoechoic mass with heterogeneous hyperenhancement in the pancreatic head. She underwent pancreaticoduodenectomy and remains disease-free to date. The second case was a 4-year-old boy with a palpable, unexplained mass in the right upper abdomen. US identified a well-defined, heterogeneous mass in the epigastric region with internal point-like hyperechoic areas. The intraoperative US showed portal vein cancer thrombus. He underwent tumor resection along with reconstruction of the portal and superior mesenteric veins. He subsequently received chemotherapy and remained disease-free to date.